2021
DOI: 10.3390/pharmaceutics13091419
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Investigation of Stereoselective Food Drug Interaction Potential of Resveratrol on Nine P450 and Six UGT Isoforms in Human Liver Microsomes

Abstract: The stereoselectivity of the food drug inhibition potential of resveratrol on cytochrome P450s and uridine 5′-diphosphoglucuronosyl transferases was investigated in human liver microsomes. Resveratrol enantiomers showed stereoselective inhibition of CYP2C9, CYP3A, and UGT1A1. The inhibitions of CYP1A2, CYP2B6, and CYP2C19 by resveratrol were stereo-nonselective. The estimated Ki values determined for CYP1A2 were 13.8 and 9.2 μM for trans- and cis-resveratrol, respectively. Trans-resveratrol noncompetitively in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 60 publications
0
9
0
Order By: Relevance
“…The inhibitory potentials of chrysophanol (IC 50 = 1.99 µM) and physcion (IC 50 = 2.16 µM) against CYP1A2 in HLMs were higher than those observed against rCYP1A2 (IC 50 = 0.29 and 0.88 µM, respectively) [16]. This could be attributed to the differences in incubation conditions, such as enzyme source (HLM versus rCYP1A2) or CYP1A2 probe substrate (phenacetin versus melatonin) [16,23]. For example, the IC 50 value of mollugin for CYP1A2-mediated POD activity in rCYP1A2 was five-fold higher than that in HLMs [27].…”
Section: Inhibition Of Cyp1a2 Activity By Five Major Phytochemicals F...mentioning
confidence: 90%
See 1 more Smart Citation
“…The inhibitory potentials of chrysophanol (IC 50 = 1.99 µM) and physcion (IC 50 = 2.16 µM) against CYP1A2 in HLMs were higher than those observed against rCYP1A2 (IC 50 = 0.29 and 0.88 µM, respectively) [16]. This could be attributed to the differences in incubation conditions, such as enzyme source (HLM versus rCYP1A2) or CYP1A2 probe substrate (phenacetin versus melatonin) [16,23]. For example, the IC 50 value of mollugin for CYP1A2-mediated POD activity in rCYP1A2 was five-fold higher than that in HLMs [27].…”
Section: Inhibition Of Cyp1a2 Activity By Five Major Phytochemicals F...mentioning
confidence: 90%
“…Electrospray ionization was performed in the positive-and negative-ion modes at 4.0 and −3.5 kV, respectively. For each metabolite, quantitation was carried out in selected reaction monitoring (SRM) mode using the following precursor-to-product ion transition: m/z 152 > 110 for acetaminophen (CYP1A2), m/z 214 > 186 for resorufin (CYP1A1 and CYP1A2), m/z 163 > 107 for 7-hydroxycoumarin (CYP2A6), m/z 256 > 238 for 6-hydroxybupropion (CYP2B6), m/z 328 > 283 for N-desethylamodiaquine (CYP2C8), m/z 287 > 89 for 5-hydroxytolbutamide (CYP2C9), m/z 362 > 214 for 4-hydroxyomeprazole (CYP2C9), m/z 258 > 157 for dextrorphan (CYP2D6), m/z 184 > 120 for 6-hydroxychlorzoxazone (CYP2E1), m/z 342 > 203 for 1 -hydroxymidazolam (CYP3A), and m/z 295 > 100 for trimipramine (IS) [23,24].…”
Section: Lc-ms/ms Analysismentioning
confidence: 99%
“…Here it is important to comment that a drug interaction effect of RSV (especially in high doses) has already been described in the literature, mainly related to drug-and carcinogen-metabolizing enzymes such as cytochrome. 35 Most studies were performed in vitro and in animal models; in humans, few studies emphasize this issue, 36 but they point out that the main negative effects in relation to RSV occur at high supplementation dosages. In clinical trials, there was observed modified pharmacokinetics of carbamazepine (a CYP3A substrate) 37 and chlorzoxazone (a CYP2E1 substrate) 38 when RSV was used for 10 days at 500 mg. High intakes of RSV have also been reported to inhibit the activity of CYP3A4 in vitro and in vivo, which metabolized drugs as 3-hydroxy3-methylglutarylcoenzyme A reductase inhibitors, calcium-channel antagonists, antiarrhythmic agents, human immunodeficiency virus protease 36 Although it has been reported that resveratrol seems to be a low-affinity substrate of CYP3A4, 39 in a clinical trial, it has observed an increase in the bioavailability of CYP3A4, a weak induction of CYP1A1 and CYP1A2, and a reduction in the activity of CYP2D6 and CYP2C9 after administering 1 g of RSV per day for 4 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Resveratrol can protect from cardiac insufficiency and cardiac fibrosis, induced by high blood pressure, by inhibiting the PTEN/AKT/Smad2/3 and NF-kB signaling pathway, resulting in heart protection. For example, it inhibits cytochrome P450 (CYP) [ 60 ].…”
Section: Wine Bioactive Compounds: Modulation Of Biochemical Pathways...mentioning
confidence: 99%